Effect of sutureless securement on hemodialysis catheter-related bloodstream infection - Keiji Fujimoto (Nature Portfolio, 2021)
Abstract The use of sutureless securement devices during catheterization might reduce the risk of catheter-related bloodstream infection (CRBSI) by suppressing catheter-exit infection and catheter dislodgement. However, the effectiveness of these devices in reducing CRBSI risk when securing hemodialysis catheters has not been explored. This single-center retrospective observational study examined 211 non-tunneled hemodialysis catheters (NTHCs) from 110 hemodialysis inpatients, of which 121 were secured using conventional skin sutures (Suture group) and 90 with GRIP-LOK (GRIP-LOK group). The stabilized inverse probability of treatment (SIPT)-weighting method was used to generate a new population (SIPT-weighted model) without group differences for each of the 12 predictors of CRBSI development (i.e., age, sex, dialysis history, concomitant acute kidney injury or diabetes, concurrent use of immunosuppressant drugs or aspirin, NTHC insertion site, methicillin-resistant Staphylococcus aureus, carriage, bacteremia event within 3 months before catheterization, hemoglobin level, and serum albumin titer). The effect of GRIP-LOK compared with sutures on CRBSI in the SIPT-weighted model was evaluated using univariate SIPT-weighted Cox proportional regression analysis, which showed a significant CRBSI suppression effect of GRIP-LOK compared with sutures (hazard ratio: 0.17 [95% CI 0.04–0.78], p = 0.023).　GRIP-LOK affords a lower risk of CRBSI due to indwelling NTHCs than conventional securement using sutures.